Faktor Faktor Penentu Loyalitas Pemain Game Online di Kalangan Milenial - Hidayat, Muhammad Syahrul (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to identify and analyze the determinants of online game player loyalty among millennials. The development of information technology and the internet has created a booming online gaming industry, with millennials being one of the main consumer segments in this industry. However, with high competition and many game options available, maintaining player loyalty is crucial to the success of game developers and providers. This research utilizes quantitative methods. Questionnaires were distributed to 173 respondents to collect quantitative data from a sample of millennial online game players. The results of data analysis show that the determinants of online game player loyalty among millennials include several aspects. First, gameplay quality and gaming experience are the main factors that influence player loyalty. In addition, interesting and quality content also contributes importantly to retaining players. Second, social interaction and in-game community support are significant factors in building emotional bonds and connections between players. Furthermore, fairness and transparency in the payment system and the ability to earn rewards and progress in the game are also determinants of loyalty. In addition, the availability of technical support and good game maintenance will increase player satisfaction and retention.